2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319256
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring game-based motor rehabilitation of patients at home for better plans of care and quality of life

Abstract: This paper describes the biomedical, remote monitoring infrastructure developed and currently tested in the EU REHAB@HOME project to support home rehabilitation of the upper extremity of persons post-stroke and in persons with other neurological disorders, such as Multiple Sclerosis patients, in order to track their progress over therapy and improve their Quality of Life. The paper will specifically focus on describing the initial testing of the tele-rehabilitation system's components for patients' biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Several studies (6668) have showed that continuing rehabilitation activities at home contributes to the maintenance of benefits obtained. Accordingly, we are developing a low-end VR tool to promote physical rehabilitation at home.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (6668) have showed that continuing rehabilitation activities at home contributes to the maintenance of benefits obtained. Accordingly, we are developing a low-end VR tool to promote physical rehabilitation at home.…”
Section: Discussionmentioning
confidence: 99%
“…We can see that a diverse range of studies/systems have been conducted/built. Some are for the upper extremity including those for arms [10,12,13,16,17,20,21,23,25,27,30,[37][38][39], hands/fingers [10, 11, 14, 17, 20, 23, 25-28, 30-33, 38], and shoulders [10-14, 16, 20-23, 27, 29, 30, 35, 38, 39], while the others are on the lower extremity including those for ankles [18,19,36], gait [15,19,24,36], balance [15,19,23,24,36], and postural [19,23,24]. However, most of these studies are conducted in laboratory setting and thus are less feasible in real clinical scenarios [1] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 5 6 ] Telemedicine services encompass a variety of services such as patient consultation, education and training of families and professionals in the area, follow-up of the patients, and monitoring of tele-services. [ 4 5 6 8 13 14 ] Recent reviews on clinical effectiveness and applications of technology in delivering effective tele-rehabilitation service and alternative interventions are limited. [ 13 15 16 ] Hence, there is a need for more trials and comprehensive studies on same issue.…”
Section: Introductionmentioning
confidence: 99%